Distribution of Cichlopsis leucogenys (Aves: Turdidae) in Brazil and its relation to protected areas - HUILQUER FRANCISCO VOGEL; MANOELE MARCOLIN BERNARDON; CLAUDIO HENRIQUE ZAWADZKI (Biodiversitas Journal of Biological Diversity, 2017)
Vogel HF, Bernardon MM, Zawadzki CH. 2017. Distribution of Cichlopsis leucogenys (Aves: Turdidae) in Brazil and its relation to protected areas. Biodiversitas 18: 1116-1121. The Rufous-brown Solitaire (Cichlopsis leucogenys Cabanis, 1851) is endangered in Brazil, and the demarcation of priority areas is needed for its in situ conservation. Accordingly, we reviewed the distribution of C. leucogenys and assessed its association with protected areas (PAs) by analyzing 70 occurrence records from 1942 to 2014 that were collected from online datasets. Of these records, 38 (54.4%) were from Bahia State, 27 (38.5%) were from Espírito Santo State, and five (7.1%) were from Minas Gerais State, and the Biological Reserve Augusto Ruschi (Espírito Santo State), State Park Serra do Conduru (Bahia State), and Serra do Ouro Environmental Protected Area (Bahia) were identified as key PAs. One record described an observation of the species at 45 m above sea level, which is lower than expected. We verified the potential occurrence of the species in 31 PAs that were located in southern Bahia to the mountains in both Espírito Santo and Minas Gerais. The Ilhéus-Itabuna region should be given special attention during conservation efforts, owing to records of species presence outside PAs, which should also be considered by management plans.